2020
DOI: 10.1051/0004-6361/202037759
|View full text |Cite
|
Sign up to set email alerts
|

Gasp

Abstract: We present atomic hydrogen (H I) observations with the Jansky Very Large Array of one of the jellyfish galaxies in the GAs Stripping Phenomena sample, JO201. This massive galaxy (M* = 3.5 × 1010 M⊙) is falling along the line-of-sight towards the centre of a rich cluster (M200 ∼ 1.6 × 1015 M⊙, σcl ∼ 982 ± 55 km s−1) at a high velocity ≥3363 km s−1. Its Hα emission shows a ∼40 kpc tail, which is closely confined to its stellar disc and a ∼100 kpc tail extending further out. We find that H I emission only coincid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 80 publications
3
49
0
Order By: Relevance
“…Black dots are H I deficient galaxies in Virgo from Corbelli et al (2012): filled symbols and empty symbols represent H 2 masses derived with constant or metallicity-dependent a CO . Finally, considering depletion times, we note that in Ramatsoku et al (2020), for JO201 and JO206, we found that H I depletion times are much shorter than the average value found in galaxy disks, apparently implying a very efficient star formation (as far as H I is concerned) and/or a low H I content for their SFR. Evaluating the global (H I + H 2 ) depletion time for the three galaxies where we have both measurements, it turns out that within the galaxy disk the estimated depletion time is in agreement with literature values (Leroy et al 2008) only for the JO206 galaxy, while JO201 and JW100 have unusually long depletion times, unless we assume extremely low values for the a CO .…”
Section: Mass Ratio Total Gas Mass Fractions and Depletion Timesmentioning
confidence: 50%
See 3 more Smart Citations
“…Black dots are H I deficient galaxies in Virgo from Corbelli et al (2012): filled symbols and empty symbols represent H 2 masses derived with constant or metallicity-dependent a CO . Finally, considering depletion times, we note that in Ramatsoku et al (2020), for JO201 and JO206, we found that H I depletion times are much shorter than the average value found in galaxy disks, apparently implying a very efficient star formation (as far as H I is concerned) and/or a low H I content for their SFR. Evaluating the global (H I + H 2 ) depletion time for the three galaxies where we have both measurements, it turns out that within the galaxy disk the estimated depletion time is in agreement with literature values (Leroy et al 2008) only for the JO206 galaxy, while JO201 and JW100 have unusually long depletion times, unless we assume extremely low values for the a CO .…”
Section: Mass Ratio Total Gas Mass Fractions and Depletion Timesmentioning
confidence: 50%
“…Having established that molecular gas is abundantly present in jellyfish galaxies, we now proceed to evaluate the proportion of the different gas phases within the galaxy disk to better characterize the star-forming cycle. Three of our galaxies (Ramatsoku et al 2019(Ramatsoku et al , 2020T. Deb et al 2020, in preparation) also possess an estimate of the H I gas content (preliminary from MeerKat data for JW100), while for the fourth one (JO204) this has been hampered by H I absorption due to the presence of a continuum source at the center of the galaxy (Deb et al 2020).…”
Section: Mass Ratio Total Gas Mass Fractions and Depletion Timesmentioning
confidence: 85%
See 2 more Smart Citations
“…This large sample has facilitated the opportunity to observe many new aspects and effects of RPS, including the possibility that RPS can funnel the gas into the central region of the galaxy, triggering and fuelling the AGN (Poggianti et al 2017a), and the widespread evidence of in-situ star formation in the tails (Poggianti et al 2019a). One of the most heavily studied jellyfish galaxies of the GASP survey to date has been JO201, analysed both individually in Bellhouse et al (2017Bellhouse et al ( , 2019, George et al (2018George et al ( , 2019, and Ramatsoku et al (2020) and as part of wider studies (Poggianti et al 2017a;Moretti et al 2018;Vulcani et al 2018;Radovich et al 2019). JO201 is a massive galaxy falling into the massive cluster Abell 85 at supersonic speeds close to the line of sight towards the observer, exhibiting signs of extreme near-face-on RPS.…”
mentioning
confidence: 99%